An Analytical Study For The Statistical Control Of The Quality Of Tartous Cement Factory Products (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research deals with an important aspect of quality control tools in industrial establishments, which is the statistical control over the quality of Tartous cement factory products to raise production efficiency, as it aims to identify the extent of clarity of the concept of quality and quality control, and to identify the methods of statistical control in monitoring the quality of Tartous cement products And showing its positive impact on improving the performance of its production processes in light of the variables of the contemporary business environment, which is characterized by intense competition, and the company's endeavor to attract customers by meeting their needs, and knowing the effect of using statistical quality control methods to identify deficiencies that hinder the achievement of this goal. The study population consisted of all the administrative workers in Tartous Cement Company, and the researcher adopted the descriptive analysis method, and the questionnaire to collect data and information from the study population consisting of 50 administrators, where 15 questionnaires were distributed, 13 valid questionnaires were retrieved and two were not valid for statistical analysis.The study concluded that there is no application of quality standards and statistical control by the administrative leadership in Tartous Cement Factory, while quality standards and statistical control are applied through the participation of workers in quality control and focus on the production process with the highest possible quality, and focus on gaining customer satisfaction Through reaching a product of high quality and standard specifications, and working on continuous improvement of the product in order to be able to compete and keep pace with local and global marketing and productivity developments. The study also confirmed that there is an application of quality standards and statistical control in general in this company, as it was found that the use of statistical control methods contributes to controlling the production process for the quality of products.